O habeas corpus coletivo como instrumento de efetivação da normatividade garantista em favor de grupos socioeconomicamente vulneráveis - Spexoto, Mario Eduardo Bernardes (2020)
This study seeks to examine the eligibility of collective habeas corpus in the Brazilian legal system, highlighting that this is imperative for promoting access to justice for those who are singled out by the punitive system in Brazil. The objective is to establish if the maximum effectiveness conferred to article 5, LXVIII, of the Federal Constitution of 1988 ensures the implementation of the guaranty standardization and if it represents an important mechanism of countermajoritarian resistance to the criminal selectivity promoted against vulnerable groups. The bibliographic analysis related to the main theoretical framework that gives support to the hypothesis is adopted as a methodology. The hypothetical-deductive reasoning is used for the development of the research. Finally, it is concluded that: the Brazilian criminal system acts preferably and selectively against vulnerable groups and, sometimes, collectively; the 1988 Federal Constitution converges with Luigi Ferrajoli's normative model of criminal guarantee; guarantee rules face obstacles to their effectiveness in Brazil; the recognition of collective habeas corpus fulfills the expectations of normative guarantee and democratically resists the selective and collectivized attack to the criminal system